Computation of verbal predicates in portuguese : relational network, lexical-conceptual structure and context : the case of verbs of movement - Amaro, Raquel (2009)
Tese de doutoramento, Linguística (Linguística Computacional), 2010, Universidade de Lisboa, Faculdade de Letras